Personalizing the Dietary Guidelines: use of a feedback report to help adolescent students plan health behaviors using a SMART goal approach. Issue 1 (1st January 2019) - Martin, Sarah; Heo, Moonseong; Jimenez, Camille C; Lim, Jean; Lounsbury, David W.; Fredericks, Lynn; Bouchard, Michelle; Herrera, Tara; Sosa, April; Wylie-Rosett, Judith
ABSTRACT: Background : School health curricula should help students choose health goals related to the Dietary Guidelines (DG) recommendations addressing obesity. We aimed to identify characteristics associated with choice of DG recommendation items. Methods : In 12 HealthCorps affiliated high schools, students completed a 19-item web-based questionnaire that provided a personalized health-behavior feedback report to guide setting SMART (Specific, Measurable, Action-oriented, Realistic, Time-bound) goals. We examined if gender, weight-status, and personalized feedback report messages were related to student-selected SMART Goals. Results : The most frequent SMART Goals focused on breakfast (22.4%), physical activity (21.1%), and sugary beverages (20.4%). Students were more likely to choose a SMART goal related to breakfast, sugary beverages, fruit/vegetable intake or physical activity if their feedback report suggested that health behavior was problematic (p < 0.0001). Males were more likely than females to set sugary beverage goals (p < 0.05). Females tended to be more likely than males to set breakfast goals (p = 0.051). Students, who had obesity, were more likely than normal weight students to set physical activity goals (p < 0.05). Conclusion : SMART goals choice was associated with gender and weight status. SMART goal planning with a web-based questionnaire and personalized feedback report appears to help students develop goals related to the Dietary Guidelines recommendations. Trial registration: ClinicalTrials.gov identifier: NCT02277496.